Hubungan antara Komunikasi Mendidik dengan Perilaku Santun Remaja pada Orang Tua Menikah Dini di Kelurahan Bungus Selatan Kota Padang - Stanggi Dewi Rahmah; Jamaris Jamaris (Universitas Negeri Padang, 2018)
This research is motivated by the number of teenagers in South Bungus Village shows behavior that is less good, which is suspected because of the way early married parents that has not seen the emotional stability in educational communication and behave in front of teenagers. This study aims to reveal the educational communication early married parents with teenagers, well behavior in early married parents, and the relationship between educational communication with teenagers well behavior in early married parents. This study used correlational research with population of all teenagers of early married parents in South Bungus Padang City by using Area Random Sampling technique. Data collection techniques used questionnaires, data collection tool questionnaire with percentage data analysis using Product Moment formula to see the relationship of both variables. The results showed that educational communication of early married parents applied to teenagers is categorized low that can be seen from the highest score found in the scores rarely, the behavior of adolescent propriety in early married parents categorized low seen from the highest score is on the score rarely, and there is a significant relationship between educational communication with teenagers well behavior in early married parents in South Bungus Padang City. Suggestions for this research is to parents who marry early to be better communicate at the time of educating children so that they can behave well and politely later.Keywords: Educational Communication, Teenagers well Behavior